X-Ray Microtomography (μCT) as a Useful Tool for Visualization and Interpretation of Shear Strength Test Results - Stefaniuk Damian; Tankiewicz Matylda; Stróżyk Joanna (Studia Geotechnica et Mechanica, 2015)
The paper demonstrates the applicability of X-ray microtomography (ìCT) to analysis of the results of shear strength examinations of clayey soils. The method of X-ray three-dimensional imaging offers new possibilities in soil testing. The work focuses on a non-destructive method of evaluation of specimen quality used in shear tests and mechanical behavior of soil. The paper presents the results of examination of 4 selected clayey soils. Specimens prepared for the triaxial test have been scanned using ìCT before and after the triaxial compression tests. The shear strength parameters of the soils have been estimated. Changes in soil structure caused by compression and shear failure have been presented as visualizations of the samples tested. This allowed for improved interpretation and evaluation of soil strength parameters and recognition of pre-existing fissures and the exact mode of failure. Basic geometrical parameters have been determined for selected cross-sections of specimens after failure. The test results indicate the utility of the method applied in soil testing.